Investigation on the Physicochemical and Mechanical Properties of Novel Alkali-treated Phaseolus vulgaris Fibers. Issue 2 (1st February 2022) - Babu, B. Gurukarthik; Princewinston, D.; Saravanakumar, S.S.; Khan, Anish; Aravind Bhaskar, P.V.; Indran, S.; Divya, D.
ABSTRACT: This investigation is aimed to analyze the effect of sodium hydroxide (NaOH) treatment on the physical, chemical, structural, thermal and surface topography of Phaseolus vulgaris fibers (PVFs). The surface of raw PVFs was modified by soaking with 5% NaOH solution for 15, 30, 45 and 60 min. The various functional groups of the alkali-treated PVFs (APVFs) were studied Fourier-transform infrared spectroscopy. The outcomes of thermogravimetric analysis evident that the optimum treatment time for 5% NaOH was 45 min. It was noticed that optimally treated PVFs have higher cellulose (69.48 wt.%), crystallinity index (52.27%) and lower hemicellulose (4.30 wt.%), lignin (7.02 wt.%) contents. The thermogravimetric analysis (TGA) of PVFs also revealing moderate thermal stability was observed; atomic force microscopy (AFM) investigation inveterates that the surface of the fiber is rough and it will be a potential reinforcement for polymer composites.